Enhancing tuberculosis treatment support: A thematic analysis of interactive messages in a digital adherence technology trial to identify needs, challenges, and strategies for improvement. - Javier Roberti; Priscilla Carmiol-Rodríguez; Enrique Chan-Liang; Omar Alfonso Aguilar-Vidrio; Agnes A Suyanto; Jennifer Sprecher; Fernando Rubinstein; Sarah Iribarren (PLoS ONE)
Background Digital adherence technologies (DATs) offer promising solutions for monitoring and supporting adherence to complex treatment regimens, including tuberculosis (TB) treatment. However, better understanding is needed of how users engage with DATs and how engagement influences their effectiveness, particularly in real-world settings and among underserved populations. Objective Assess user engagement with the Companion app within the Tuberculosis Treatment Support Tools (TB-TST) intervention and explore the types of interactions that promote treatment adherence and address patients' needs. Methods Secure message threads (N = 255) were analyzed as part of a four-site pragmatic clinical trial evaluating the effectiveness of the TB-TST intervention. Pragmatic thematic analysis was applied to chat logs between patients and treatment supporters (TSs) to identify key themes related to application utilization, treatment adherence, technical challenges, and communication patterns. Results Key themes that emerged included: experiences of living with TB; COVID-19 pandemic impact; symptom guidance, healthcare coordination, and treatment and intervention adherence and technical issues. Patients frequently sought advice on how to integrate TB treatment into their daily lives, manage side effects, and cope with emotional distress. The communication styles of TSs varied, with personalized and empathetic interactions leading to better patient acceptance. Technical issues and difficulties accessing phone credit and connectivity challenges were barriers to intervention adherence. Recommendations from this analysis emphasize the need for personalized communication, streamlined adherence reporting, timely symptom guidance, expanded mental health support, and improved healthcare coordination to strengthen the intervention. Conclusion This study highlights the importance of personalized, empathetic communication, and reliable technology to enhance the effectiveness of DATs. Future DAT solutions should prioritize technological reliability and the human elements of care. Interventions must be adaptable, user-friendly, and capable of addressing diverse patient needs, including offering emotional support and empowering individuals with limited digital literacy.